Development of robotic rover with controller & vision system - Roshahliza M Ramli; Nurul Aqilah Herman; Muhammad Ridzuan Mazlan; Azlin Suraya Nazaruddin; Muhammad Arshad Tuah; Abdul Naqib Eizzaz Abd Samad; Kamal Othman; Yanti Marliana Esmail (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Rover is a robotic system that integrates a simple system implementing electrical and mechanical components together. In this study, we propose a rover using mechanical components which consist of a robotic arm, joint and mechanical gripper, backbone chassis and continues track, while the electrical components include servo motor, servo controller, transmitter and receiver for vision system and wireless controller via USB host as its control system. The purpose of this project is for monitoring and safety purposes. In addition, the main goal of this project is to develop a simple robotic rover that is easy to build and manufacture as well as cost-effective. To add more functionality on this rover, it is equipped with a robotic arm and real-time view camera integration. This rover is equipped with a first-person view (FPV) camera, an integrated camera on the rover that can give clear visibility and direction to the rover pilot. The live feed can be viewed on the monitor inside the command station box. It can be used to assist safety authorities to collect information & insights, work lift to collect and remove the load and to conduct search and rescue operation. As for the result, the mobility system of the robotic rover at terrain surfaces and analyses the capabilities of the chassis during lifting load had been tested.